A3.33 Increased rho-kinase activity in temporal artery biopsies from patients with giant cell arteritis. (31st January 2014) - Lally, Lindsay; Narula, Navneet; Pernis, Alessandra B; Huang, Wei-Ti; Udeh, Uzunma; Spiera, Robert F
Abstract : Background/Purpose: ROCKs are implicated in the pathogenesis of many vascular diseases. ROCK activation is associated with Th17 differentiation and production of Th17-associated cytokines, IL-17 and IL-21. Th17 cells and related cytokines are present in increased levels in active Giant Cell Arteritis (GCA). ROCK activity in GCA is unknown. The aim of this study was to assess ROCK activity in temporal artery biopsy (TAB) specimens in GCA versus controls. Methods: All TAB performed at a tertiary care center over a 5 year period were identified. Charts were reviewed for clinical information. Subjects were categorised according to 1990 ACR criteria and TAB status into 3 groups: GCA with positive TAB, GCA with negative TAB and age-sex-matched controls. Paraffin-embedded temporal artery specimens were stained for Phospho-Ezrin/Radixin/Moesin (pERM), a surrogate of ROCK activity, using immunohistochemical stain. pERM stained slides were reviewed by a pathologist blinded to clinical status. Three separate areas (endothelium, adventitia and vaso vasorum) were scored for intensity of staining on a scale of 0-2 for total possible composite score of 6. Primary outcome was biopsy pERM intensity score in subjects with GCA compared to controls. Results: Nineteen subjects with GCA had positive TAB, 17 subjects had GCA with negative TAB and18 age-sex-matched controls were analysed. Mean age was 77.9 ± 9.1years and 81.4% were female with no differences in baseline demographics between the 3 groups. Compared to controls, GCA subjects with either positive or negative TAB had significantly higher pERM intensity scores (p = 0.0159). Adjusting for diabetes, hypertension, prednisone, and statin use, GCA subjects still had higher pERM intensity scores (OR 7.3; 95% CI 1.9–25.9, p = 0.0046). Comparing GCA with negative TAB to controls, high pERM score had sensitivity of 90.4% and negative predictive value of 90.9%. Conclusion: Subjects with GCA had more intense pERM staining in TAB specimens compared to age- sex-matched controls regardless of whether TAB was positive or negative, suggesting increased ROCK activity in GCA. High pERM staining score had a sensitivity higher than the sensitivity of routine TAB histopathology itself, suggesting it may be a useful adjunctive diagnostic tool in patients with negative TAB. The ROCK pathway warrants further investigation in GCA as it may be of both diagnostic and therapeutic significance.